Small animal disease surveillance: GI disease and salmonellosis. (2nd September 2017) - Arsevska, Elena; Singleton, David; Sánchez‐Vizcaíno, Fernando; Williams, Nicola; Jones, Philip H.; Smyth, Steven; Heayns, Bethaney; Wardeh, Maya; Radford, Alan D.; Dawson, Susan; Noble, Peter J. M.; Davies, Robert H.
Abstract : Presentation for gastrointestinal (GI) disease comprised 2.2 per cent of cat, 3.2 per cent of dog and 2.2 per cent of rabbit consultations between April 1, 2016 and March 31, 2017 Diarrhoea and vomiting without blood were the most frequently reported GI disease clinical signs (34.4 and 38.9 per cent in cats and 42.8 and 37.3 per cent in dogs, respectively) The mean percentage of samples testing positive for Salmonella in dogs was double that in cats (0.82 per cent and 0.41 per cent, respectively) from January 1, 2011 to December 31, 2016 In dogs, autumn was associated with a greater proportion of Salmonella ‐positive sample submissions; no clear suggestion of seasonal variation in cats was observed In both cats and dogs, isolates belonging to Salmonella enterica group B serotypes were the most common (68.9 per cent in cats and 55.0 per cent in dogs)